Political Participation in West Nusa Tenggara Governor Election 2013. - Mega Rizky Savitri (IPEM 14 UMY 093, 2014)
*93 Non-voters behavior (abstentions) is frequently occur on the Direct Regional Head Election in Indonesia. In West Nusa Tenggara Province, the number of voters who did not invoke their right to vote are become increase. On West Nusa Tenggara Governor Election 2008, the number of voters who choose to be abstains are reach 25,05% from total number of registered voters. Meanwhile, on West Nusa Tenggara Governor Election 2013, the â€œWhite Groupâ€ are increase about 29,54%. The high number of voters who did not invoke their voting right shows the decreasing of votersâ€™ participation. This research aimed to determine the level of political participation of community in West Nusa Tenggara Governor Election 2013. This research is focused on the measurement of the political participation level in the form of conventional political participation. In addition, this research is also aims to know peopleâ€™s assessments toward their chosen candidates of Governor and Deputy Governor in West Nusa Tenggara Governor Election 2013. Either West Nusa Tenggara Voters are categorized as rational voters or not. Moreover, this research conducted in order to learn factors/reasons of societies in their bearing to become non-voters (abstentions). Quantitative Method by use survey as the main method, added by Qualitative Method by use in-depth interview is made the results of this research are clear and meaningful rather than only use one method. The results of this research that political participation level of society in West Nusa Tenggara Province are categorized as low. Results of this research show that 61% respondents did not actively participate in the West Nusa Tenggara Governor Election 2013 Stages. Meanwhile, the most common form of political participation done in people live is giving vote for one of the candidates of Governor and Deputy Governor in West Nusa Tenggara Governor Election 2013. Voters who have voted one of the candidates are categorized as rational voters. Furthermore, there are 31% respondents in this research who did not use their voting right in West Nusa Tenggara Governor Election 2013. The reason to become abstains is in disbelief that the candidate governor and deputy governor will fulfill their promises that has been declared during the campaign processes. It is recommended for the next researcher to conduct the next research that is intended to examine the statistic in order to prove the reality in West Nusa Tenggara Province. In addition, it is also recommended to carry out other research that examine about how far the influence of non-voters behavior toward the decreasing of voters participation, in a different perspective.